Effect of the concentration of inoculum and tensoactive on the efficiency of Bipolaris sorokiniana infection in wheat leaves - Reis,Erlei Melo (2014)
Techniques that result in increased pathogen infection rates by employing reduced quantities of fungal spores with sparse sporulation have been developed. Experiments under controlled environment conditions were conducted to evaluate the effect of the density of Bipolaris sorokiniana conidia on the intensity of wheat helminthosporiosis. Using a selected inoculum density, the concentration of the tensoactive (Tween 20) that promoted maximum infection by the causal agent of the disease was determined. The density of lesions and the estimated severity of the disease were quantified. The selected inoculum density was 1.5 x 10(4) spores.mL-1 plus 480 µL tensoactive.L-1 water, resulting in a disease severity that allows selecting wheat cultivars resistant to B. sorokiniana.